PEMANTAPAN AJARAN ISLAM DALAM BUDAYA BUGIS-MAKASSAR - Wahyu, Wahyuddin (RIHLAH, 2013)
This paper reveals the phenomenon of South Sulawesi cummunity in looking at the custom. Bugis and Makassar society upholds and believes contains customary sanctity, generous nature, and sanctity. Basically is honesty and knowledge, being the aim is to benefit all the people, liked by people and received it with all willingness democratically. Therefore, it may not be changed much less canceled. The King with people already has been witness it to the Gods after confirmed as a permanent custom. Upon the acceptance of Islam (sara) became an integral part of panngadareng (customary system), the Bugis and Makassar social institutions acquire new colors, so that their obedience to sara together with their adherence to other aspects panggadareng